PENGARUH TINGKAT KEPUASAN PENGUNJUNG TERHADAP KINERJA PELAYANAN PETUGAS TAMAN MINI INDONESIA INDAH JAKARTA - Arief, Andi Moh. Rifiyan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
Research done with descriptive method korelasioner and assisted by the way ofdistributing questionnaires to vositors who next data procesing using a likert.From the discussion that there is then obtained correlation value (r) of 0,8576, which meanthere is a very strong/ high among the service performance of officers of the level of visitorsatisfaction in this area. Coefficient of determination of 73,55%. This can be said thatperformance of service by Taman Mini Indonesia Indah influenced by the level of satisfactionof visitors and the rest equal to 24,45%, Taman Mini Indonesia Indah officer performance isinfluenced by other factors such as who was has not studied the work environment and motivation.